Key factors to consider in the placement of dental resins in adults at Hospital Bernardo Sepúlveda, Mexico - Rodríguez-Pérez, Anais; Baldovinos-Leyva, Irma; García-Serna, Erick; Loyo-Salgado, Daniela (Revista Acciones Médicas, 2023)
The increasing demand from patients seeking aesthetic restorations underscores the importance of comparing standardized general parameters with the techniques employed by various dental professionals. This study specifically focused on the application of composite resins in filling 20 dental structures affected by grade 1 caries. The methodology adopted is descriptive-explanatory, supported by data collected from the literature and a structured questionnaire in accordance with NOM-004-SSA3-2012. Additionally, a detailed anamnesis was conducted for each patient with the purpose of integrating considerations regarding the preventive needs of asepsis and antisepsis in treatment. Contrasting the data reveals that nanotechnology is playing a significant role in the development of new dental biomaterials. It is crucial to consider specific factors, such as individual pathologies and elements that may interfere with the composite placement protocol. This comparative analysis between official parameters and current practices provides valuable insights into trends and advancements in the field of aesthetic restorations with composite resins.
Keywords: factors; caries; dental resins; patients